Interprofessional collaborative practice in the treatment of HIV among pregnant women: a scoping review - Rima Muliani; Sulistyaningsih Sulistyaningsih (Universitas Aisyiyah Yogyakarta, 2022)
Background : The occurrence of HIV among pregnant women has an impact on the process of pregnancy and childbirth which further leads to the need for interprofessional collaborative practices between health workers in the treatment of HIV among pregnant women. Objective : The aim of this study was to scrutinize the interprofessional collaborative practices in the treatment of HIV among pregnant women. This was achieved by clarifying if and how implementation of scientific study was used in the interprofessional collaborative practices in the treatment of HIV among pregnant women. Method : To map relevant literature, a scoping review was conducted to articles published between January 2015 and December 2020, guided by a method consists of five stages approach. Specifically, the following academic databases were systematically searched to identify publications that presented findings on identifying scoping review questions with the PEOS framework (Population, Exposure, Outcome, Study Design), identifying relevant articles using the PubMed, Scopus, Science Direct, and Grey Literature (Google Scholar) Information about each study was extracted using a purposely designed data extraction form and database with keyword with keywords, carrying out the Critical Appraisal using Hawker tools, charting and compiling data, summarizing and reporting results. Results : Of the 60 articles with relevant titles and abstracts, 4 articles were identified to meet the inclusion and exclusion criteria with grade A. Besides, four themes were found, namely roles, barriers, interpersonal communication, and patient-centred services in the interprofessional collaborative practices of HIV treatment among pregnant women. Conclusion : The role of midwives and doctors was indispensable in implementing informed consent, counseling, HIV screening, and HIV treatment training. The barriers encountered by midwives and doctors were the lack of clinical skills, limited infrastructure such as teaching aids for training, the lack of funding budget from policy makers, and the lack of communicative competence. As suggestion for the next review, this review could submit register review protocols-namely, PROSPERO and the Joanna Briggs Institute to ascertain by searching databases and the online platforms of organizations.